Uncovering Reflective Practices of Educators In Teaching and Learning Process: a Phenomenological Study from Elementary School in The Philippines - Eleanor Tandang Abelilla (RSF Press, 2024)
Recent PISA results consistently show that 15-year-old students in the Philippines are five (5) to six (6) years behind in critical competencies, including mathematics, science, and reading—issues that predate the pandemic. Given teachers' enormous influence on students' academic success, the efficacy of their teaching tactics is becoming increasingly important. The advent of the epidemic and adjusting to a new normal posed significant hurdles to established information transfer techniques. This study investigates the reflective practices of educators at Los Baños Central Elementary School, Philippines, analyzing the evolution of these practices across three key periods: pre-pandemic, during the pandemic, and in the post-pandemic